Special endurance rating in freestyle wrestling - Kuzmina, S. S.; Abramova, V. R.; Sivtsev, N. N.; Korkin, E. V. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to assess benefits of a test system to estimate special endurance in freestyle wrestlers including the blood lactate and lipid peroxidation rating test designed by the instructors of Churapcha State Institute of Physical Education and Sports (CSIPES) for application in a pre-season within an annual training cycle. Highly skilled (Candidate Masters and Masters of Sport) students (n=23) of CSIPES were subject to an experiment. The peripheral blood lactate was tested by an Accutrend Lactate analyzer (Roche Diagnostics); and the interim products of lipid peroxidation including the malone dialdehide (MDA) and low-molecular anti-oxidizing agents were tested in the blood serum by the common spectrophotometric methods. The post-training-cycle test data showed progress of the sample in the specific working capacity and special endurance rates, with the highest progress tested as a result of the CSIPES-designed test. The lactate variations showed progress in the bodily glycolytic process in the subject training stage indicative of the special endurance improvement. As found by the study, the physical working capacity may be improved by the anti-oxidizing correction of the lipid peroxidation activation process associated with high-intensity physical activity.